SAPAAN NAMA DALAM RELASI KELUARGA DAN MASYARAKAT JAWA DAN FUNGSINYA DALAM PEMBELAJARAN BAHASA JERMAN - Sahayu, Wening (Diksi, 2006)
AbstractThis article is based on a paper aiming at describing (1) a classification ofgreetings by name based on form and interpersonal relationship in the life of theJavanese society and family, (2) the norms used in greetings by name ininterpersonal relationships within the Javanese society and family, and (3) thefunction of the usage of such greetings in the teaching and learning of German.The is biased on data compiled by means of a method of listening andspeaking with baiting techniques and analyzed by means of intralingual andextralingual comparative methods. To distinguish extralingual factors, acomponential analysis was used. Norms of alternation and co-occurrence werealso used to determine greeting alternatives.The results are that (1) in form the greetings by name used by the subjectsunder study can be differentiated into phonological and syntactical ones:shortened name, name of endearment, kinship term plus name, kinship term plusprofession/rank/degree plus name, nickname, and adult name, (2) the norms usedare of two types, alternation and co-occurrence, and (3) a study on greetings byname in the Javanese society can function as a provider of items for comparison ina study on German and particularly for the subject matter of KontrastiveKulturkunde.Keywords: greetings by name, Javanese society, GermanA.